The adaptive value of density-dependent habitat specialization and social network centrality - Webber, Quinn M. R.; Laforge, Michel P.; Bonar, Maegwin; Vander Wal, Eric (Nature communications, 2024)
Density dependence is a fundamental ecological process. In particular, animal habitat selection and social behavior often affect fitness in a density-dependent manner. The Ideal Free Distribution (IFD) and niche variation hypothesis (NVH) present distinct predictions associated with Optimal Foraging Theory about how the effect of habitat selection on fitness varies with population density. Using caribou ( Rangifer tarandus ) in Canada as a model system, we test competing hypotheses about how habitat specialization, social behavior, and annual reproductive success (co)vary across a population density gradient. Within a behavioral reaction norm framework, we estimate repeatability, behavioral plasticity, and covariance among social behavior and habitat selection to investigate the adaptive value of sociality and habitat selection. In support of NVH, but not the IFD, we find that at high density habitat specialists had higher annual reproductive success than generalists, but were also less social than generalists, suggesting the possibility that specialists were less social to avoid competition. Our study supports niche variation as a mechanism for density-dependent habitat specialization. Social behavior and habitat specialization are often linked through density-dependence and their effects on fitness. Here, the authors show that in caribou, these traits are density-dependent, but only habitat specialization has an effect on fitness.